2013
DOI: 10.31729/jnma.565
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Care of Type 2 Diabetes

Abstract: Introduction: Biologically male and female have similar diabetes prevalence. Gender differences in the social structure bring differences in life style modifications and all other self care behaviors in type 2 diabetes. The primary purpose of this study was to assess the gender difference in care of type 2 diabetes in Western region, Nepal.   Methods: Hundred men and hundred women respondents participated in a cross-sectional study conducted in two hospitals in Pokhara, Nepal. A pre-tested questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
3
16
1
Order By: Relevance
“…However, there are few studies about sex differences in chronic diseases. Small observational studies have shown some differences in the diagnosis and treatment of diabetes mellitus and epilepsy in Nepal and India, respectively, but not in the acute setting [23,24]. This highlights the need for further study in the management and outcomes of acute manifestations of noncommunicable, chronic diseases in India.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies about sex differences in chronic diseases. Small observational studies have shown some differences in the diagnosis and treatment of diabetes mellitus and epilepsy in Nepal and India, respectively, but not in the acute setting [23,24]. This highlights the need for further study in the management and outcomes of acute manifestations of noncommunicable, chronic diseases in India.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the multidimensional, self-care regimen is challenging (Zulman, Rosland, Choi, Langa, & Heisler, 2012) and places a significant burden on physical and mental well-being (Wang, Wu, & Hsu, 2011). Various external factors like availability of social support, psychological factors such as self-efficacy (Hunt, Grant, & Pritchard, 2012;Strom & Egede, 2012), socioeconomic factors (e.g., low income, employment status; Debussche, Balcou- Debussche, Besancon, & Traore, 2009), demographic factors (e.g., gender, religion, marital status, educational status, expectation regarding aging [ERA]; Kart, Kinney, Subedi, Basnyat, & Vadakkan, 2007;Karter et al, 2007;Kiberenge, Ndegwa, Njenga, & Muchemi, 2010;Shrestha, Kosalram, & Gopichandran, 2013), cultural factors (Nam, Chesla, Stotts, Kroon, & Janson, 2011;Shrestha et al, 2013), and disease-related factors (like presence of DM-related complications, presence of comorbidities; Song et al, 2012) have been identified to affect self-care behaviors of adults with DM.…”
Section: Self-care Behaviorsmentioning
confidence: 99%
“…24 Men were less likely to have inappropriate dietary practices than women with family support. 23 In this study, gender, education, duration of diabetes and adult education favorably affected HbA1c, fasting plasma glucose, and body weight. The effect of predictors like men, aging adults, having a moderate-income group, and a higher education group, longer duration of diabetes and had a lower glycemic control benefited from the exposure to the multi-modality strategies by the diabetes nurse educators.…”
Section: Effectiveness Of Multi-modality Strategiesmentioning
confidence: 56%
“…22 Gender differences in diabetes process of care have also been observed in a few studies. 23,24 More women tend to adhere to self-care (healthy diet, glucose monitoring, and self-foot examination) compared to men. However, women tend to be inactive due to gendered differentiated roles and socio-cultural norms compared to their counterparts.…”
Section: Effectiveness Of Multi-modality Strategiesmentioning
confidence: 99%